A companion of Dragomir’s generalization of Ostrowski’s inequality and applications in numerical integration - Alomari, M. W. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
λ) f(x) - ^b_a f(t)dt]| ≤ ≤[(b-a)^24(λ^2 + (1 - λ)^2) + (x - a + b2)^2] ||f’||_∞ are established. Some sharp inequalities are proved. An application to a composite quadrature rule is provided.